2016
DOI: 10.1021/acsami.6b04213
|View full text |Cite
|
Sign up to set email alerts
|

Dual Influence of Reduction Annealing on Diffused Hematite/FTO Junction for Enhanced Photoelectrochemical Water Oxidation

Abstract: Band structure engineering of the interface between the semiconductor and the conductive substrate may profoundly influence charge separation and transport for photovoltaic and photoelectrochemical devices. In this work, we found that a reduction-annealing treatment resulted in a diffused junction through enhanced interdiffusion of hematite/FTO at the interface. The activated hematite exhibited higher nanoelectric conductivity that was probed by a PeakForce TUNA AFM method. Furthermore, charge accumulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 59 publications
5
25
0
Order By: Relevance
“…For the CH 3 NH 3 PbI 3 thin film, a negative TPV signal means that it is a p-type semiconductor [43] due to the accumulation of photoinduced electrons at the surface. The recombination time of photoinduced electrons is about 6×10 −4 s. Completely different from the TPV result of CH 3 NH 3 PbI 3 , a positive signal observed from the CuBiI 4 thin film suggested that the CuBiI 4 material is an n-type semiconductor [44,45], which is in good agreement with the UPS result. Importantly, the recombination time of the CuBiI 4 thin film is about 1×10 −3 s, which signifies an even longer life time of photoinduced charge carrier of CuBiI 4 than that of CH 3 NH 3 PbI 3 .…”
Section: Resultssupporting
confidence: 71%
“…For the CH 3 NH 3 PbI 3 thin film, a negative TPV signal means that it is a p-type semiconductor [43] due to the accumulation of photoinduced electrons at the surface. The recombination time of photoinduced electrons is about 6×10 −4 s. Completely different from the TPV result of CH 3 NH 3 PbI 3 , a positive signal observed from the CuBiI 4 thin film suggested that the CuBiI 4 material is an n-type semiconductor [44,45], which is in good agreement with the UPS result. Importantly, the recombination time of the CuBiI 4 thin film is about 1×10 −3 s, which signifies an even longer life time of photoinduced charge carrier of CuBiI 4 than that of CH 3 NH 3 PbI 3 .…”
Section: Resultssupporting
confidence: 71%
“…However, its performance has been severely limited by low electrical conductivity, poor charge separation, and transfer efficiency (short hole diffusion length of 2-4 nm), and sluggish oxygen evolution reaction kinetics. [1][2][3][4] These shortcomings significantly affect the free carriers formation and migration involved in a typical PEC water splitting process, including free carrier excitation by light absorption, transportation to the electrode surface, collection at the back electrode, and transfer to the solid/electrolyte interface for water oxidation. [5][6][7] Therefore, a number of approaches including doping, cocatalyst decoration, morphology engineering, R E T R A C T E D highly conductive and photoactive α-Fe 2 O 3 photoanodes by thermal decomposition of FeOOH in an oxygen-deficient atmosphere (e.g., N 2 /air, Ar).…”
Section: Water Splittingmentioning
confidence: 99%
“…Hematite (α‐Fe 2 O 3 ) is regarded as one of the most promising photoanodes for photoelectrochemical (PEC) water splitting because of its chemical stability, earth abundance, and favorable optical band‐gap (≈2.1 eV) that allows for light harvesting of ≈40% of the solar spectrum. However, its performance has been severely limited by low electrical conductivity, poor charge separation, and transfer efficiency (short hole diffusion length of 2–4 nm), and sluggish oxygen evolution reaction kinetics . These shortcomings significantly affect the free carriers formation and migration involved in a typical PEC water splitting process, including free carrier excitation by light absorption, transportation to the electrode surface, collection at the back electrode, and transfer to the solid/electrolyte interface for water oxidation .…”
mentioning
confidence: 99%
“…37,38 Doping methods and nanofabrication techniques are heavily investigated in regard to the effect on the nal performance, [38][39][40] but there is still ample room to investigate the exact mechanisms that cause the improvement: for example, it is well known that annealing improves the hematite water splitting efficiency, 22,41 but the diffusion of the dopant into the material from a substrate or a surface decoration as a consequence of the annealing, is investigated more rarely. 24,42,43 In parallel, when the dopant is the main subject of interest, controllable yet elaborate methods are employed. 11,44,45 In the present study, a relatively simple method leads to a diverse ensemble of effects at once, ranging from the diffusion of different dopants, to the modication of the electrode structure morphology, to the addition of functional groups to the outer surface.…”
Section: Introductionmentioning
confidence: 99%